2016
DOI: 10.1039/c6ra02988d
|View full text |Cite
|
Sign up to set email alerts
|

Invasin-functionalized liposome nanocarriers improve the intracellular delivery of anti-infective drugs

Abstract: Intracellular infections caused by invasive pathogens continue to prove difficult to combat, due in part to the commonly poor membrane permeability of anti-infective drugs. The aim of this study was to improve the intracellular delivery of one such poorly permeable (but broad-spectrum) anti-infective, gentamicin. Gentamicin was encapsulated into liposomal nanocarriers which were then surface functionalized with InvA497, a bacteria-derived invasion protein. Treatment of HEp-2 cells infected with the enteroinvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Nanoparticle formulations were then incubated with HEp-2 cells to determine the cellular uptake. A previous study conducted with liposomal nanoparticles functionalized with the same InvA497 invasin fragment has shown an increased cellular uptake due to the presence of InvA497 on the surface of such nanocarriers ( 3 , 9 ); in accordance with this observation, InvA497 functionalization of both spherical and aspherical nanoparticles in the current work enhanced their uptake and internalization into epithelial cells, as confirmed by both CLSM (Fig. 3 ) and FACS analysis (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nanoparticle formulations were then incubated with HEp-2 cells to determine the cellular uptake. A previous study conducted with liposomal nanoparticles functionalized with the same InvA497 invasin fragment has shown an increased cellular uptake due to the presence of InvA497 on the surface of such nanocarriers ( 3 , 9 ); in accordance with this observation, InvA497 functionalization of both spherical and aspherical nanoparticles in the current work enhanced their uptake and internalization into epithelial cells, as confirmed by both CLSM (Fig. 3 ) and FACS analysis (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Aspherical and spherical nanoparticles were then surface-functionalized with InvA497, a C- terminal fragment of the Yersinia-derived invasion protein invasin. As observed previously ( 3 , 5 , 9 ), the uptake of spherical delivery systems functionalized with InvA497 is enhanced due to the presence of this bacterial protein on particle surfaces; it was therefore of interest to see whether the same effect was noted with an aspherical delivery system. In order to bind to the β 1 integrin receptor on epithelial cells and mediate internalization, the C- terminal carboxyl group of InvA497 must remain free and project outwards from the particle surface.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…26 In a follow-up study, Menina and collaborators showed that the invasin-functionalized liposomes loaded with the model antibiotic gentamycin had a greater antimicrobial effect on intracellular Y. pseudotuberculosis and Salmonella enterica in HEp-2 epithelial cells when compared to non-functionalized liposomes, due to their surface modification. 27 This approach indicates that taking advantage of the natural bacterial invasion characteristics may aid in enhancing the antibacterial activity of drugs that have poor permeability, such as gentamycin.…”
Section: Bioengineered Liposomes As Carriers For Antibioticsmentioning
confidence: 99%